Community Service Interventions Determine Rural Business Expansion And Consumer Awareness: Intervensi Pengabdian Masyarakat Menentukan Ekspansi Bisnis Pedesaan Dan Kesadaran Konsumen - Evie Destiana; Nargadio Rakhmadani Putra; Rachmad Aditya Alfaris; Deva Amirotul Khusnah; Fitri Novianty (Proceedings of The ICECRS, 2025)
General Background Micro, small, and medium enterprises constitute a fundamental economic pillar requiring continuous innovation to survive global market competition. Specific Background Rural commercial operators in Begaganlimo Village struggle with constrained financial capital, low commercial literacy, and an inability to build strong brand identities. Knowledge Gap Despite the acknowledged necessity of visual identity, practical implementation mechanisms for resource-limited rural enterprises utilizing university community service programs remain underexplored. Aims This qualitative case study investigates how university student interventions facilitate commercial capacity building through targeted product rebranding initiatives. Results In-depth interviews and participant observations reveal that modernizing logo designs, upgrading functional product packaging, and developing online social media narratives successfully modernized the local commercial identity. Consequently, these specific interventions directly triggered increased product sales, elevated commercial visibility, and built substantial entrepreneur confidence in competitive online environments. Novelty This research isolates the specific participatory mechanisms where academic community service transitions from theoretical advisory roles to tangible digital and physical visual identity execution. Implications Government stakeholders and educational institutions must integrate continuous digital training, stakeholder collaboration, and regular monitoring into future empowerment frameworks to ensure sustainable local economic development. Highlights: Modernized packaging designs and contemporary logos successfully trigger higher product sales. University student guidance effectively transitions traditional merchants into modern online platforms. Continuous training and collaborative monitoring guarantee long-term local economic sustainability. Keywords: Micro Enterprise Empowerment, Product Rebranding, Digital Marketing, Qualitative Case Study, Brand Identity